Feasibility and Safety of Video Endoscopic Inguinal Lymphadenectomy in Vulvar Cancer: A Systematic Review. - Chai-E Liu; Yan Lu; De-Sheng Yao (PLoS ONE)
Objective To systematically review previous studies and to evaluate the feasibility and safety of video endoscopic inguinal lymphadenectomy (VEIL) in vulvar cancer. Methods We conducted a comprehensive review of studies published through September 2014 to retrieve all relevant articles. The PubMed, EMBASE, Web of Science, Cochrane Library, Wan Fang Data and Chinese National Knowledge Infrastructure databases were systematically searched for all relevant studies published in English or Chinese through September 2014. Data were abstracted independently by two reviewers, and any differences were resolved by consensus. Results A total of 9 studies containing 249 VEIL procedures involving 138 patients were reviewed. Of the 249 VEIL procedures, only 1 (0.4%) was converted to an open procedure for suturing because of injury to the femoral vein. The range of operative time was 62 to 110 minutes, and the range of estimated blood loss was 5.5 to 22 ml. The range of the number of harvested lymph nodes was 7.3 to 16. The length of hospital stay varied from 7 to 13.6 days across reports. The incidence of lymph node metastasis was 19.7% (27/138), and the recurrence rate was 4.3% (3/70) within 3 to 41 months of follow-up. One or more short-term complications were documented in 18 of 138 (13.0%) patients. Complications after VEIL were observed in 14 (10.13%) patients and in 15 (6.0%) of the VEIL cases, including major lymphocyst formation in 9 (3.6%), lymphorrhea in 2 (0.8%), inguinal wound infection without wound breakdown in 3 (1.2%) and lymphedema in 1 (0.4%). Conclusions VEIL appears to be a feasible procedure in the management of vulvar cancer. There may be potential benefits that result in lower morbidity compared to traditional methods, but this has yet to be objectively proven.